Life under stalin - Adendorff, Jo ([S.l.] : History Films Pty Ltd. [production company] [S.l.] : Classroom Video, 1999, 1999)
Discover about polite and social life under Stalin government
Executive producer, John Davis ; editor, Phil Sheppard
Keywords: Stalin, Joseph, -- 1879-1953; Russia -- History; Russia -- Politics and government